The Role of Diagnostic Hysteroscopy in Evaluation of Intrauterine Adhesions in Infertile Females - Rabia Bashir; Fauzia Anjum; Razia Ghafoor; Sara Rasool; Sundes Jawaid Khokar; Yousaf Latif Khan (Pakistan Journal of Medical Research)
Background: Sub-fertility is a growing reproductive health concern. While common causes like PCOS and endometriosis are well-known, intrauterine adhesions (IUAs) remain an under recognized contributor. Intrauterine adhesions, often resulting from uterine surgeries, can impair fertility and are best diagnosed through hysteroscopy.